Role of intranasal midazolam as a procedural sedative in children aged 6 months to 12 years: An open-label randomized controlled study - Subhash, Swathy; Joji, Prameela (Indian Journal of Child Health, 2018)
Objectives: The objectives of the study were to evaluate the efficacy and the adverse effects of intranasal midazolam compared to intravenous (IV) midazolam for procedural sedation in children between 6 months and 12 years of age using the University of Michigan sedation scale. Design: Prospective open-label randomized controlled trial. Setting: Children requiring sedation for any invasive or non-invasive procedure in the Department of Paediatrics, between June 2012 and May 2014. Participants: A total of 246 children aged between 6 months and 12 years of age were enrolled and sequentially allocated into the study by computer-generated block randomization. Intervention: As per randomization, participants were administered intranasal or IV midazolam before the procedure. Procedure was done 5 min after IV and 15 min after intranasal administration. Main outcome measures: Sedation score was rated using the University of Michigan Sedation Score. The ease of performance, numbers of successfully completed procedures, and adverse effects were noted. Results: Intranasal midazolam provided better sedation scores (p